Development of Teaching Modules for Negotiation Texts based in Online Buying and Selling Shopee - Surahya, Dela Oktaviona; Rahmawati, Laili Etika (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research aims to develop teaching modules for negotiation texts by assessing the existing condition of teaching modules at SMA Negeri 1 Baturetno and identifying students' needs. The method utilized is Research and Development, aiming to create supplementary products that refine previous versions. Data collection involves interviews with educators, student needs surveys via questionnaires, and observation of the current teaching module. The findings indicate that the previous teaching module was imperfect due to its separate arrangement and various shortcomings, such as lacking identity, learning outcomes, structured flow, motivation, and adaptation to contemporary times and technology. Results from the student needs survey demonstrate that 80% of students strongly agree, and another 20% agree that the teaching modules used are engaging and alleviate learning tension. Moreover, 60% strongly agreed with the necessity of motivation provision before learning, and 80% strongly agreed with incorporating ice breakers. Students' preferred learning styles are visual and auditory, with 45% strongly agreeing and 55% agreeing that the teaching module adequately adapts to modern times. Validation was conducted by Indonesian language teachers using nine assessment indicators, resulting in a 94% rating, categorizing it as "very valid." Based on the validation outcomes, it can be concluded that the development of negotiation text teaching modules focused on online buying and selling at Shopee is successful.